Selection of tool transverse speed considering trial run experimentations for AZ61/Tic composite developed via friction stir processing using triangular tool. (2021) - Sagar, P.; Handa, A.
Abstract: In this present work, an effort has been applied to fabricated AZ61/TiC magnesium based metal matrix composite. The effect of tool transverse speed and specimen holding time after etchant application has been studied before final design and run of experiments. A set of zig-zag holes were prepared into the 200 mm × 100 mm × 6 mm thick AZ61A plate and compacted with TiC particles. A fixed three pass Friction stir processing (FSP) was performed out employing a fixed tool rotation speed of 850 rpm and varying tool transverse speed of 25 mm/min, 100 mm/min and 170 mm/min. Optical microscopy (OM) was used to study the grain refinement. The results indicate that for tool rotational speed of 850 rpm and transverse speed of 25 mm/min better grains were formed at stir zone (SZ) and poor grains were observed once the specimen analyzed after 25 min of etching.